CAPACITY ANALYSIS OF RESERVOIR BUILDING AND CLEAN WATER DISTRIBUTION IN LEMBANG BUA' TARRUNG, REMBON DISTRICT TANA TORAJA DISTRICT - Reni Oktaviani Tarru; Harni Eirene Tarru; Yephta Biu' Padatuan (Media Bina Ilmiah, 2023)
Lembang Bua' Tarrung is one of the Lembang in the District Rembon Tana Toraja Regency and has 4 hamlets , namely Merrara Hamlet , Buttu Hamlet , Karappa ' Lebusan Hamlet, and Lebani ' Tiroallo Hamlet . Lembang Bua' Tarrung is area hills and have cool climate . _ In the area this , number growth population Keep going increase every year so that the need for clean water will also Keep going increase . In Buttu Hamlet there is a reservoir building serving community water needs with a volume of 12.5 m3 and distributed with 50 mm (2 in ) diameter PVC pipe , will but the available water in this reservoir not yet distributed by equally to all society , so study this aim for knowing capacity adequate reservoir and pipe size as channel distribution of clean water in Lembang Bua' Tarrung. Method in study this is method quantitative with count maximum water requirement in order to determine capacity reservoir building and water demand at peak hours for determine pipe size as channel clean water distribution. Research results show that capacity reservoir building 25% of maximum water requirement , which is 32.4 m3 with dimensions of 3.6 m × 3 m × 3 m. Distribution pipe with a diameter of 3 inches HDPE type . 8 hydrants general dotted service with each with a capacity of 23.1 m3.